Identification of a novel paternally expressed transcript adjacent to snRPN in the Prader-Willi syndrome critical region. - Ning, Y; Roschke, A; Christian, S L; Lesser, J; Sutcliffe, J S; Ledbetter, D H (Genome Research, 1996)
Small nuclear ribonucleoprotein-associated polypeptide N (snRPN) and an anonymous transcript, PAR-5, are two of the paternally expressed transcripts mapped to the Prader-Willi syndrome critical region. Using long-range PCR, we have isolated the genomic interval between snRPN and PAR-5, identified a novel transcript in this region, and termed it PAR-SN. Northern analysis demonstrates that PAR-SN is expressed in brain, skeletal muscle, and heart. Like snRPN and PAR-5, PAR-SN is expressed exclusively from the paternal homolog in cultured lymphoblasts. Sequence analysis of the transcript revealed no significant open reading frame but did include a polymorphic dinucleotide repeat (CA)17.
10.1101/gr.6.8.742